Innovative Drug Delivery Systems: The Role of Dendrimers - D, Londhe Punam; Ajay, Fugate; Shinde, Vijay; Sadule, Akshay; Jadhav, Komal (Asian Journal of Pharmaceutical Research and Development, 2025)
Dendrimers, highly branched and monodisperse macromolecules, have emerged as promising nanocarriers for drug delivery due to their unique structural and physicochemical properties. This review highlights the fundamental aspects of dendrimers, including their architecture, synthesis methods, and mechanisms of drug delivery. Dendrimers' internal cavities allow drug encapsulation, while their surface functional groups facilitate covalent conjugation and targeted delivery. Various types of dendrimers, such as PAMAM, PPI, and PEGylated dendrimers, offer versatility in addressing challenges like poor solubility, controlled release, and biocompatibility. The integration of dendrimers into modern drug delivery systems has opened avenues for precision medicine and enhanced therapeutic outcomes. This review aims to provide a comprehensive understanding of dendrimers and their potential in advancing drug delivery technologies.